Comparison of the efficacy of vaginal micronised progesterone tablet and gel for in vitro fertilisation - Soo Jin Han; Hoon Kim; Yun Soo Hong; Sung Woo Kim; Seung-Yup Ku; Chang Suk Suh (Journal of Obstetrics and Gynaecology)
Background Luteal phase support (LPS) with progesterone is a generally accepted practice after controlled ovarian stimulation, although the best protocols for LPS have been debated. We aimed to compare the efficacy of vaginal micronised progesterone tablets and 8% vaginal progesterone gel for LPS using real-world data.Methods This retrospective study included 459 in vitro fertilisation/intracytoplasmic sperm injection cycles performed at a university hospital from 2005 to 2019. All cycles were followed by fresh day 3 embryo transfer (ET). Either progesterone tablets or gel was used for LPS. To control the conditional probability of progesterone tablets or gel use, doubly robust inverse probability weighting composed of inverse-probability-of-treatment weighting (IPTW) and regression adjustment (RA). IPTW was performed based on the covariate balancing propensity score (CBPS).Results Progesterone tablets were administered in 65 cycles, and progesterone gel was administered in 394 cycles. Women who used progesterone tablets were more likely to be older (36 vs. 34 years), have primary infertility (78.5% vs. 61.4%), use gonadotropin-releasing hormone antagonist (60.0% vs. 43.2%), and have fewer retrieved oocytes (seven vs. nine) and transferred embryos (two vs. three) than participants who used progesterone gel. After IPTW-CBPS and RA analysis for the above covariates, the adjusted odds for clinical pregnancy in women who used progesterone tablets were 1.10 times compared with women who used progesterone gel; however, the 95% confidence interval did not reach statistical significance (0.96–1.26).Conclusions Clinical pregnancy was comparable between vaginal micronised progesterone tablets and vaginal progesterone gel for LPS in fresh day 3 ET cycles.